How adding the abdominal massage to polyethylene glycol can improve symptom and quality of life in patients with functional constipation in comparison with each one of the treatment modalities alone: A randomized clinical trial. (August 2020) - Mokhtare, Marjan; Karimi, Shahdieh; Bahardoust, Mansour; Sotoudeheian, Mohammadjavad; Ghazi, Ayoub; Babaei-Ghazani, Arash
Highlights: Previously a variety of medical and non-medical treatments have been introduced for functional constipation relief. A combination of abdominal massage and PEG treatment will result in more improvement in the symptoms of functional constipation. Implication of abdominal massage as an adjunct treatment and in combination with other therapeutic modalities is beneficial. A combination of abdominal massage and PEG is safe, tolerable and more effective than each one of the treatments alone. Abstract: Background: A variety of medical and non-medical treatments have been introduced for functional constipation relief. Here, we aimed to compare the efficacy of a combination of polyethylene glycol (PEG) and abdominal massage with each one of the treatments alone. Materials and methods: Patients with functional constipation based on Rome IV criteria were randomly assigned into the three treatment groups: group A (abdominal massage for 15 min daily), group B (PEG 20 g daily), and group C (PEG 20 g plus abdominal massage for 15 min daily) for 14 days. PAC-QOL questionnaire, Bristol stool scale were evaluated at baseline and two weeks after treatment. Constipation-associated symptom scores were recorded at baseline, two weeks and four weeks after treatment beginning. Descriptive statistics were provided as the mean ± standard deviation or number and percentage. P-value<0.05 was considered statistically significant. Results: Forty eight, 47 and 48 patients in group A, B, and C completed the study, respectively. PAC-QOL, Bristol and Constipation-associated symptom scores showed a significant improvement in all study groups two weeks after the treatment compared to the baseline. At the end of treatment, the rate of straining, incomplete evacuation sensation, finger evacuation and the number of defecation was significantly lower in the group C (P < 0.04). Bristol score were significantly improved in group B (P = 0.029) in compare to other groups. The total quality of life score was also significantly improved in the group C (P = 0.028). Conclusion: A combination of abdominal massage and PEG is safe, tolerable and more effective than each one of the treatments alone.